2019
DOI: 10.1016/j.ultsonch.2018.12.007
|View full text |Cite
|
Sign up to set email alerts
|

The secondary Bjerknes force between two oscillating bubbles in Kelvin-Voigt-type viscoelastic fluids driven by harmonic ultrasonic pressure

Abstract: The interaction between two small bubbles experiencing transient cavitation in a nonlinear Kelvin-Voigt fluid is investigated. The time-delay effect in the interaction is incorporated in the coupled Keller-Miksis model. The refined model predicts that bubbles with radii smaller than 2µm will be repelled by large bubbles, in contrast to predictions from previous models. The matching pressure needed to obtain same level of transient cavitation in different Kelvin-Voigt fluids is shown to depend mainly on the she… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 44 publications
1
15
0
Order By: Relevance
“…Specifically, the expansion ratios of bubbles can be suppressed or enlarged, which largely depends on the ultrasound parameters, the ambient bubble radii, the distances between bubbles and the number of bubbles [35] , [39] , [40] . Recently, several studies have attempted to clarify the impacts of the viscoelasticity of the surrounding medium on the translational and/or radial motions of bubbles with considering bubble–bubble interactions [41] , [42] . It was found that increasing elasticity, viscosity or both would significantly reduce the translational and radial motions of bubbles and consequently reduce the bubble–bubble interactions [42] .…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the expansion ratios of bubbles can be suppressed or enlarged, which largely depends on the ultrasound parameters, the ambient bubble radii, the distances between bubbles and the number of bubbles [35] , [39] , [40] . Recently, several studies have attempted to clarify the impacts of the viscoelasticity of the surrounding medium on the translational and/or radial motions of bubbles with considering bubble–bubble interactions [41] , [42] . It was found that increasing elasticity, viscosity or both would significantly reduce the translational and radial motions of bubbles and consequently reduce the bubble–bubble interactions [42] .…”
Section: Introductionmentioning
confidence: 99%
“…For example, the wave will be greatly attenuated by the oscillating bubbles within a short distance [33][34][35], leading to the frequency locking of the wave [34]. On the contrary, the acoustic wave could also manipulate the distributions of the bubbles through inducing the Bjerknes forces between them [36][37][38][39], leading to the coalescence of the bubbles. In the present model, for the sake of the simplicity, those effects are not accounted with neglecting the strong interactions between the waves and bubbles.…”
Section: Discussionmentioning
confidence: 99%
“…The pressure wave travels with a finite speed c, so the time for the pressure to propagate from bubble i to j is D i j /c. If this time-delay effect is taken into account in the pressure coupling term, [7] shows that Eq. 3becomes…”
Section: The Governing Equationsmentioning
confidence: 99%
“…Note that the two summations on the right hand side include every term from j = 1 to N. Eq. (5) was given in a slightly different form in [7]. Eq.…”
Section: The Governing Equationsmentioning
confidence: 99%
See 1 more Smart Citation